SPRED1 mutations (Legius syndrome): another clinically useful genotype for dissecting the neurofibromatosis type 1 phenotype. Issue 7 (13th May 2009) - Spurlock, G; Bennett, E; Chuzhanova, N; Thomas, N; Jim, H-Ping; Side, L; Davies, S; Haan, E; Kerr, B; Huson, S M; Upadhyaya, M
Abstract : Objective: Mutations of the SPRED1 gene, one of a family of Sprouty (Spry)/Spred proteins known to "downregulate" mitogen activated protein kinase (MAPK) signalling, have been identified in patients with a mild neurofibromatosis type 1 (NF1) phenotype with pigmentary changes but no neurofibromas (Legius syndrome).To ascertain the frequency of SPRED1 mutations as a cause of this phenotype and to investigate whether other SPRED / SPRY genes may be causal, a panel of unrelated mild NF1 patients were screened for mutations of the SPRED1-3 and the SPRY1-4 genes. Methods: 85 patients with a mild NF1 phenotype were screened for S PRED1 mutations. 44 patients negative for both NF1 and SPRED1 mutations were then screened for SPRED2-3 and SPRY1-4 mutations. Complexity analysis was applied to analyse the flanking sequences surrounding the identified SPRED1 mutations for the presence of direct and inverted repeats or symmetric sequence elements in order to infer probable mutational mechanism. Results: SPRED1 mutations were identified in 6 cases; 5 were novel and included 3 nonsense (R16X, E73X, R262X), 2 frameshift (c.1048_c1049 delGG, c.149_1152del 4 bp), and a single missense mutation (V44D). Short direct or inverted repeats detected immediately adjacent to some SPRED1 mutations may have led to the formation of the microdeletions and base pair substitutions. Discussion: The identification of SPRED1 gene mutation in NF1-like patients has major implications for counselling NF1 families.